SPICY AND MEDICINAL PROPERTIES OF SAFFRON (CROCUS SATIVUS) PLANT - Nasiba Abdunazarovna Yuldasheva (European Science Publishing, 2024)
This article provides information on the systematic role of saffron plant, medicinal and spice properties, its practical importance in food, pharmaceuticals, porphyumeria and the national economy.
Keywords: saffron, anticancerogenic, antimutagenic, red gold.